Hyperproduction of Proinflammatory Cytokines by WSX-1-Deficient NKT Cells in Concanavalin A-Induced Hepatitis - Atsushi Yamanaka; Shinjiro Hamano; Yoshiyuki Miyazaki; Kazunari Ishii; Atsunobu Takeda; Tak W. Mak; Kunisuke Himeno; Akihiko Yoshimura; Hiroki Yoshida (2004)
Abstract Administration of Con A induces liver injury that is considered to be an experimental model for human autoimmune or viral hepatitis, where immunopathology plays roles mediated by activated lymphocytes, especially NK1.1+ CD3+ NKT cells, and inflammatory cytokines, including IFN-γ and IL-4. In the present study we investigated the role of WSX-1, a component of IL-27R, in Con A-induced hepatitis by taking advantage of WSX-1 knockout mice. WSX-1-deficient mice were more susceptible to Con A treatment than wild-type mice, showing serum alanine aminotransferase elevation and massive necrosis in the liver. Although the development of NKT cells appeared normal in WSX-1 knockout mice, purified NKT cells from the knockout mice produced more IFN-γ and IL-4 than those from wild-type mice in response to stimulation with Con A both in vitro and in vivo. In addition, hyperproduction of proinflammatory cytokines, including IL-1, IL-6, and TNF-α, was observed in the knockout mice after Con A administration. These data revealed a novel role for WSX-1 as an inhibitory regulator of cytokine production and inflammation in Con A-induced hepatitis.